On the Possibility of Istiqb?l al-Qibla on a Sphere Earth - Arangül, Muammer (Erciyes Üniversitesi, 2019)
We, as the contemporary Muslims, who believe that we should both face qibla while praying and live on a sphere globe, found ourselves probably in a paradox, which we are not aware of. That the shape of the world is a globe was engraved in our subconscious through the visuality of either an apple or an orange since the years of primary school. When we asked ourselves or our teachers ‘’Well then, why don’t we drop down?’’ by imagining ourselves most of the time as very small bats, hanged on a huge ball from the legs, it was ‘’law of gravity’’ that lent a helping hand to us and our curiosity was satisfied to some extent. I call it “to some extent” because either the shape of the world or the law of gravity was not something that each of us experience or observe individually. What most of us did was just to rely on those, who say that they visited space or moon and took the pictures of the world therefrom or that performed several studies, observations and tests about the respective issues. It was neither something that came to our minds individually to make any observation or tests about the shape of the world or think deeply about this matter nor was it something that each of us could cope with. In order to be able to do so, it was both required to have advanced level of information in many fields and expensive technological instruments, which will not be vouchsafed to everybody. Therefore, as in many other disciplines, what we all did was to understand and rationalize ‘’in our own way’’ what was told to us about these issues. We somehow accepted that the world is spherically shaped and left it aside as an apodictic information and ignored to a large extent the fact that such recognition may contradict with any religious order. As the Muslims, who are the object of the following order; “So turn your face toward al-Masjid al-Haram. And wherever you [believers] are, turn your faces toward it [in prayer].” (al-Baqarah 2/144) and that are requested to turn their faces towards al-Masjid al-Haram while praying, we always kept away from confronting the following question; “how possible is it to turn our faces towards al-Masjid al-Haram in a world, shaped spherically?”. As one of the Muslims, who believe in both of these two seemingly contradicting things together to say the least, it was likewise a surprising thing to see the confusion on the face of anybody, whom I asked this question that personally mixed up my mind. Unfortunately, the researches, which I made in the hope of finding a ready book, article, study or letter that will save me from struggling desperately among the sources of Islamic Law, also remained inconclusive. Probably the most serious study, conducted in this respect, was the article, called “The Correct Qibla” of Abdali that tried to prove that it is possible to face towards qibla on a spherical world; however, there were also some problems, that this article failed to resolve. While reviewing many sources of Fiqh in the hope of finding a brilliant idea or an interesting opinion regarding how I could turn my face towards al-Masjid al-Haram on a global world, it remained all the time in my mind that religious scholars were likely to have solved this problem completely, by not insisting that much on facing towards qibla while praying thereby misinterpreting qibla verse on the other hand. What should be emphasized initially is that this issue should be addressed in the literature under the title of “istiqbal al-qibla” (Facing towards Qibla) rather than “istiqbal al-qibla” (Facing towards Ka´bah) because the borders of the qibla are much more wider than that of the Ka´bah. However, when the literature is reviewed, it is easily remarkable that essential qibla is the Ka´bah. The factor to extend the qibla, which in fact consists of Ka´bah, ‘’horizontally’’ rightward or leftward is the fact that Ka´bah could not be seen and that ‘’facilitation’’ principle is put into action in regard to the possibility that Ka´bah may be missed despite all the efforts displayed thereof. Therefore, a ‘’deviation’’ at a limited rate towards the right or left of Ka´bah was taken for granted, but it had always been emphasized that this was a deviation. It is ‘’possible’’ to face towards Ka´bah on a horizontal surface. When it comes to vertical dimension, some phrases are encountered in Fiqh books stating that “from the seven layers of ground to the seven layers of sky up to the Throne’’ is qibla. That the altitude of Abu Qubais mountain in Macca is higher than Ka´bah and that it is not possible for someone, who is praying on this mountain, that Ka’´bah faces towards that person, had an impact on scholars to have such an opinion. Authorization to pray on Abu Qubais mountain or on a building foundation, which was dug out lower than Ka´bah in Macca, was a factor that extended the border of qibla in ‘’vertical’’ dimension as well. However, extension of the borders of qibla vertically towards the bottom and top of Ka´bah is not an essential situation and the essential qibla is nevertheless Ka´bah; that is to say; it is inappropriate for someone, who is praying at the bottom of, or near the Ka´bah, to extend his/her face or body downward or upward  from Ka´bah arbitrarily. Well then, does the vertical or horizontal extension of the borders of qibla to a considerable extent, unless of course accidental or non-essential reasons or due to facilitation principle, make it ‘’possible’’ in a global world to face towards Ka´bah, or towards the qibla in the widest sense? In accordance with the mathematics of earth curvature based on the spherical shape of the world, Ka´bah, which is 13 meters in height, drops below the horizon line and disappears approximately after 18 km even when the average human length is calculated as 2 meters. Not that much far, but; even when it is just 18 km away from Ka´bah, facing towards Ka´bah becomes impossible for a person who is 2 meters in length. Even if we give up the fact that Ka´bah is the essential qibla and consider that the entire 45’ degree angle to the right and left of the Ka´bah in horizontal dimension as well as seven layers of the ground under Ka´bah to the seven layers of the sky above the Ka´bah up to the Throne is the “essential” qibla, the concept of the world that can be inferred from the books of Fiqh can only be a “hemisphere”. In a world, which is spherical in shape, it is only possible to face towards a qibla on a hemisphere where Ka´bah is located in the center of the same. It becomes impossible and insignificant to face towards qibla as soon as such hemisphere is extended. In my opinion, the order of Islam regarding qibla contradicts with what modern scientists tell about the shape of the world. As the Creator knows the shape of the world  and God will never order something impossible, what should be done is to get rid of the following contradiction in which we both accept that the world has a spherical shape and that it is possible to turn towards qibla with our face and body while praying. In my article, it is addressed in detail through scientific, reasonable and quoted evidences why it is impossible to turn towards qibla on a round world; it is further indicated that what should be done is to question the accuracy of the scientific data and opinions but not what is required by the verse and it is stated as the most substantial and absolute result that “To intend something impossible invalidates that intention.”
Küre Bir Dünyada İstikbâl-i Kıblenin İmkanı Üzerine